Custom Law: Address to the New Zealand Society for Legal and Social Philosophy - Durie, E T (Victoria University of Wellington Law Review, 1994)
The author was then the Chief Judge of the Māori Land Court and Chairperson of the Waitangi Tribunal. He is of Ngāti Kauwhata, Ngāti Raukawa and Rangitāne descent. The text is a paper delivered to the New Zealand Society for Legal and Social Philosophy at Victoria University of Wellington on 22 July 1994. The author introduces the laws of Māori to a non-Māori audience by providing a framework for a distinctive set of values that collectively constituted the Māori legal order. He begins with the constraints on the development of a custom law study. He then discusses the nature of customary law, noting that it reflects the social and political order of the people. The author also argues that a study of Māori land tenure was more than likely to reveal a substantial religious philosophy due to their long-standing personal connections to their land and whakapapa. The author concludes by lamenting the lack of a comprehensive study of Māori law as a science at the time.